THE PHENOMENON OF CYBERCHONDRIA AND MISINFORMATION ON ONLINE MEDICAL FORUMS - Piotr Helbin; Aleksandra Gralec; Piotr Tryczyński; Jakub Wrona; Jakub Sałak; Sebastian Ożga; Wiktoria Donocik; Katarzyna Szlachetka (International Journal of Innovative Technologies in Social Science, 2026)
Background: Universal internet access has reshaped health information seeking. In environments with unregulated algorithms, easy access to user-generated content often devolves into compulsive diagnosis-seeking, fueling cyberchondria. Online medical forums foster echo chambers where misinformation gains a status equal to scientific evidence. Objective: The aim of this scoping review is to provide a critical analysis of the relationship between the architecture of misinformation on health-related online forums and the escalation of cyberchondria. Methods: This article is a comprehensive scoping review conducted in accordance with the PRISMA guidelines. Leading scientific databases, including PubMed, Web of Science, Scopus, and APA PsycINFO, were systematically searched. Due to the diversity of the collected studies, a thematic narrative synthesis method was applied. Results: Recommendation algorithms create echo chambers that amplify health anxiety, with "super-spreaders" generating most harmful content. Misinformation exploits cognitive biases, such as the availability of heuristic and intolerance of uncertainty. The analysis highlights the "eHealth literacy paradox," where advanced digital skills without medical knowledge exacerbate cyberchondria. Compulsive information seeking also exhibits characteristics of behavioral addiction via variable reinforcement. Conclusion: Cyberchondria is no longer solely an individual disorder, but a systemic phenomenon driven by forum architecture. Countering it requires an interdisciplinary approach, integrating technological tools (e.g., AI models) to identify misinformation cascades and enhancing users’ digital health competencies.